QUALITY OF LIFE OF EMPLOYEES IN THE BRAZILIAN FEDERAL EDUCATION NETWORK (CIPEEX, 2025)
The quality of life (QoL) of civil servants, teachers, and administrative staff in the Brazilian federal education network is a determining factor for individual well-being and institutional efficiency. This study is a cross-sectional epidemiological study that aimed to evaluate the factors that influence the QoL of civil servants in the Brazilian federal education network. We used the WHOQOL-bref instruments in association with a sociodemographic questionnaire. This study was conducted in 2022, involving 1,563 administrative staff and teachers from the Brazilian federal education network. The approach adopted was cross-sectional and epidemiological in nature. For statistical analysis, we used the Student's t-test and analysis of variance (2-way ANOVA), followed by post hoc analysis (Tukey) for three or more factors (α=0.05). Teachers reported better QoL in environmental terms when compared to administrative technicians (p
Keywords: Administrative staff; Teachers; Quality of life